GAMBARAN TENTANG KESENJANGAN DIGITAL ORANG TUA DAN ANAK DAN RANCANG BANGUN INTERVENSI SOSIAL – DIGITAL - Luahambowo, Terserah (Jurnal Insani, 2020)
This article answers two research questions: (i) what is the picture of the digital divide caused by the use of digital technology in Bejiarum Village, Wonosobo City, and (ii) what can be done to develop interventions to address the digital divide? To answer these two questions, methods and interviews and Focused Group Discussions were used to collect information, which was carried out flexibly during the 10-day stay in Wonosobo. The answer to question one shows that ownership and use of digital technology is evenly distributed, there is almost no gap between children and parents. While the answers to question two indicate the need to develop an organization for the use of digital technology at the RW (Citizens Association) level through the RT (Neighborhood Association)-based WiFi program.